PEMANFATAN E-COMMERCE DALAM MEMBANTU PEMASARAN PRODUK PERTANIAN BAGI USAHA TANI DI KOTA MAKASSAR - Suharyadi Rahmat; Muhammad Hasan; Citra Ayni Kamaruddin; Nurdiana Nurdiana; Nur Arisah (Jurnal Riset Entrepreneurship, 2022)
This study aims to find out and observe how the online marketing system is carried out by KWT Orchid located in Bara Baraya Village, Makassar District, Makassar City, South Sulawesi. This research is a type of qualitative research with a qualitative descriptive method. Respondents who were sampled in this study were members of the Orchid KWT. The sampling technique used in this study used a purposive sampling technique. Test the validity of the data using the source triangulation process. The results of the study explain that KWT Orchid has actually implemented online sales, However, online marketing is still limited, only using wa where farmers interact with sellers through wa if someone wants to buy. Even then, they are still relatives or family of this KWT member. In addition, KWT Orchid has collaborated with Grab to market products.